Enhancing EFL Students' Recount Text Writing Through Project Based Learning: A Classroom Action Research Study in an Indonesian Junior High School - Lewina Pulcher Simanungkalit; Jenita Anjani Br. sembiring; Junita Siahaan (English Lecturers and Teachers Association (ELTA), 2026)
Improving English writing skills continues to be a critical issue in Indonesian junior high schools, particularly in writing personal recount texts. A baseline assessment conducted at SMP St. Thomas 3 Medan highlighted that students faced significant language challenges, particularly in organizing chronological events and using past tense, and showed minimal interest in writing activities. This study aimed to address these challenges by implementing a Project-Based Learning (PjBL) approach to improve students' recount writing skills and stimulate increased classroom engagement. Using a Classroom Action Research (CAR) framework, the study spanned two cycles and involved 31 eighth-grade students. Information was collected through written evaluations, observation forms, and surveys to assess students' academic performance and engagement levels. Results indicated that the implementation of PjBL resulted in significant improvements in writing skills. The average student writing score increased from 54.12 in the initial learning cycle to 86.00 in the final learning cycle, and the overall mastery percentage increased significantly from 22.5% to 93.54%, effectively exceeding the Minimum Completion Criteria (KKM). Furthermore, survey data showed that students strongly preferred Project-Based Learning (PBL) because it encouraged teamwork and meaningful educational experiences. These results suggest that Project-Based Learning (PBL) is an effective teaching method for improving students' conceptualization and writing skills, and provide valuable information for teachers aiming to increase student participation and writing achievement in EFL classrooms. These findings underscore the potential of PBL to transform traditional writing instruction into a more dynamic and engaging student-centered process, offering practical solutions for educators facing similar challenges in EFL environments. By fostering a collaborative environment, PBL not only improves linguistic skills in writing narrative texts but also increases students' confidence and motivation. Keywords : project-based learning (PjBL); writing skills; recount text; classroom action research